Empirical Investigation Of The Relationship Between Islamic Concept Of Al-Raja (Hope) And Higher Institution Students' Mental Well Being - Uswatun Hasanah; Sri Nurul Milla; Ismail Abdul Fatai (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
The present research is an attempt to investigate the relationship between the concept of al-Raja [hope] as spiritual aspect in Islamic worldview and mental well-being. The study employs quantitative research method where 1045 higher institutions students were surveyed through administration of questionnaire. The Pearson moment correlation analysis was conducted with SPSS version 21 to investigate the relationship. The finding from the analysis shows that there is significant positive correlation between Islamic concept ofal-Raja (Hope) and student's mental well-being. The study provides implication for religious Islamic religious adherents as well as Muslim psychotherapist to see the Islamic concept of Raja as a factor that can boost individual mental state. Keywords : Mental health, well-being, al-raja (hope)